Characterization of Statin Dose Response in Electronic Medical Records. Issue 3 (4th October 2013) - Wei, W‐Q; Feng, Q; Jiang, L; Waitara, M S; Iwuchukwu, O F; Roden, D M; Jiang, M; Xu, H; Krauss, R M; Rotter, J I; Nickerson, D A; Davis, R L; et al.
<x xml:space="preserve">Abstract</x> Efforts to define the genetic architecture underlying variable statin response have met with limited success, possibly because previous studies were limited to effect based on a single dose. We leveraged electronic medical records (EMRs) to extract potency (ED50) and efficacy (Emax) of statin dose–response curves and tested them for association with 144 preselected variants. Two large biobanks were used to construct dose–response curves for 2, 026 and 2, 252 subjects on simvastatin and atorvastatin, respectively. Atorvastatin was more efficacious, was more potent, and demonstrated less interindividual variability than simvastatin. A pharmacodynamic variant emerging from randomized trials (PRDM16) was associated with Emax for both. For atorvastatin, Emax was 51.7 mg/dl in subjects homozygous for the minor allele vs. 75.0 mg/dl for those homozygous for the major allele. We also identified several loci associated with ED50. The extraction of rigorously defined traits from EMRs for pharmacogenetic studies represents a promising approach to further understand the genetic factors contributing to drug response. Clinical Pharmacology & Therapeutics (2014); 95 3, 331–338. doi:10.1038/clpt.2013.202